Experimental aortic valve heterotransplantation. Issue 6 (November 1967) - Duran, C. G.; Gunning, A. J.; Whitehead, R.
Abstract : Pig aortic valves were transplanted into the descending aorta of 41 dogs. Ficin-digested valve grafts and fresh untreated grafts were associated with poor results and extremely short survival of the recipient animals. When freeze-dried valves were transplanted the mortality was reduced and the survival time increased, but there was a marked tendency for the grafts to rupture through the heterologous aortic wall cuff. If a homologous aortic cuff was used the survival time was increased, but rupture through the aortic wall cuff still occurred. The freeze-dried valve grafts eventually became almost acellular. Thrombus, which was commonly present on the valves, rarely showed organization. The valve cusps tended to remain thin and delicate, in one dog for as long as eight months after operation.